The caregiving experience: How much do health professionals understand? - Wynaden, Dianne; Ladzinski, Urusula; Lapsley, Jennifer; Landsborough, Ian; Butt, Janice; Hewitt, Vivien (Royal College of Nursing Australia, 2006)
Legal, social and economic factors have changed the delivery of care to people who have a mental disorder. Many of these people are now treated in the community and they live with or in close proximity to their family. The aim of this paper is to provide health professionals with an insight into the experience of being a caregiver to a person with a mental disorder. For these families caregiving becomes an integral part of everyday life.Positive outcomes for both the caregiver and the ill family member are more likely to occur when effective levels of collaboration exist between health professionals and caregivers. Collaboration is enhanced when caregivers and health professionals value each other's contribution to the ill family member's care. Often the burden, stress, and socio-economic effects on the family caring for a person with mental illness is not sufficiently appreciated and further increases this burden. A review of the literature from the caregiver's perception is presented. An increased understanding of the caregiving experience will enable health professionals to develop and implement strategies that facilitate positive outcomes for the caregiver and the ill family member.